Efektivitas Ekstrak Daun Eceng Gondok Eichornia crassipes Sebagai Bahan Antikanker pada Sel Tumor MCF-7 dengan Metode In Vitro dan In Silico - Eva Johannes; Andi Ilham Latunra; Mustika Tuwo; Sry Sukmawaty (Universitas Hasanuddin, 2021)
The use of water hyacinth Eichhornia crassipes bioactive compounds has been developed, including as an anti-cancer base material. This study aims to examine the potential of water hyacinth leaf extract on MCF-7 tumor cells with the MTT method and the affinity of the water hyacinth leaf compound using molecular docking methods. The results showed the effect of water hyacinth leaf extract on MCF-7 cancer cell death due to the active compounds stigmasterol and phytol, while the docking results showed the best binding affinity value on stigmasterol and its receptor 1QR1 which was -9.4.